2005
DOI: 10.1007/s00542-005-0563-z
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology advances and applications in information storage

Abstract: A brief review of some applications of nanotechnology to information storage is given with the focus on self-assembled nanoporous alumina templates for patterned media.Ordered nanoporous alumina templates were fabricated by self-assembly technology. A two-step anodization process was also carried out to obtain templates with pores perpendicular to the substrate without removing the aluminum and barrier layer. Polycrystalline structure was observed with a grain size of about 2 lm in which the pores were almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In contrast, we did not observe such kind of disadvantages in the bottom side of the PAA film as shown in the HRSTEM image. Many researchers (Masuda and Fukuda, 1995; Masuda et al, 1997b;Juang and Bogy, 2005;Zhang et al, 1998) reported that growth rate of pores, pore density, pore ordering and pore clarity increase with increase in anodizing time. It has also been reported that there is no effect on growth rate of pores and pore density decrease with increase in anodizing time after critical anodizing time (Feiyue et al, 1998).…”
Section: Resultsmentioning
confidence: 96%
“…In contrast, we did not observe such kind of disadvantages in the bottom side of the PAA film as shown in the HRSTEM image. Many researchers (Masuda and Fukuda, 1995; Masuda et al, 1997b;Juang and Bogy, 2005;Zhang et al, 1998) reported that growth rate of pores, pore density, pore ordering and pore clarity increase with increase in anodizing time. It has also been reported that there is no effect on growth rate of pores and pore density decrease with increase in anodizing time after critical anodizing time (Feiyue et al, 1998).…”
Section: Resultsmentioning
confidence: 96%
“…Tissue engineering has emerged as a potential alternative to tissue transplantations and aims to develop biological substitutes to repair damaged tissues and restore their functionality using a triad of cells (usually stem cells), biomaterial scaffolds, and soluble factors . Every year, world's population is remarkably increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is a great demand in the microelectronics industry for the ideal magnetic medium consisting of a 2D array of ordered islands with nanometer dimensions. Patterned magnetic media fabricated directly by various lithography techniques and regular arrays of magnetic dots and wires obtained by a template synthesis approach have been one of the more widely discussed possibilities for useful devices to extend the density of recording and information storage [21][22][23][24][25][26]. Magnetic structures have been also used for the fabrication of a nanoscale single domain magnetoresistive bridge sensor, and for a new ultra-high-resolution tip of the magnetic force microscope [27].…”
Section: Introductionmentioning
confidence: 99%